2007
DOI: 10.1007/s10479-006-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Capacitated lot sizing and scheduling with parallel machines and shared buffers: A case study in a packaging company

Abstract: The aim of this work is to propose a solution approach for a capacitated lot sizing and scheduling real problem with parallel machines and shared buffers, arising in a packaging company producing yoghurt. The problem has been formulated as a hybrid Continuous Set-up and Capacitated Lot Sizing Problem (CSLP-CLSP). A new effective two stage optimisation heuristic based on the decomposition of the problem into a lot sizing problem and a scheduling problem has been developed. An assignment of mixture to buffers is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 35 publications
0
31
0
2
Order By: Relevance
“…The objective in the mathematical models is to minimize the inventory and backlog costs, as well as the number of setup changeovers in the filling lines (each change implies a small penalty in the objective function). The third term in the objective function is of a second order in comparison with the first two terms (observe that the value of alpha is a sufficiently small number; see function (1)). This small penalty aims at ensuring that, among the minimum cost solutions (first two terms), the optimal solution results in a small number of setup changeovers in periods with idle capacity.…”
Section: (I) Liquid Preparation (Stage I)mentioning
confidence: 99%
See 1 more Smart Citation
“…The objective in the mathematical models is to minimize the inventory and backlog costs, as well as the number of setup changeovers in the filling lines (each change implies a small penalty in the objective function). The third term in the objective function is of a second order in comparison with the first two terms (observe that the value of alpha is a sufficiently small number; see function (1)). This small penalty aims at ensuring that, among the minimum cost solutions (first two terms), the optimal solution results in a small number of setup changeovers in periods with idle capacity.…”
Section: (I) Liquid Preparation (Stage I)mentioning
confidence: 99%
“…Integrated lot-sizing and scheduling (sequencing) are a widely studied area [1,2]. The recent literature reviews by Almada-Lobo et al [3] and Copil et al [4] highlight an increasing interest in simultaneous lot-sizing and scheduling problems in many companies, resulting in researches motivated by industrial practical applications, such as glass container [5], animal nutrition [6], soft drink [7], wood floor [8], pulp and paper mill [9], food [10], automotive applications [11], supermarkets [12], and thin film transistor and liquid crystal display [13].…”
Section: Introductionmentioning
confidence: 99%
“…The lot-sizing and scheduling problems have been widely used in several productive sectors (e.g., Araujo et al, 2008;Almada-Lobo et al, 2008;Luche et al, 2009;Toso et al, 2009;Santos & AlmadaLobo, 2012;Marinelli et al, 2007;Kopanos et al, 2010, among many others). Some studies are found in the production of non-alcoholic drinks such as soft drinks, water, tea and juice, but most of these studies consider soft drink production lines.…”
Section: Introductionmentioning
confidence: 99%
“…Since Araujo et al (2007), many other authors have also researched the intergrated lot-sizing and sequencing problem, with material preparation at a prior stage, in a wide range of industrial settings, for example, in soft drink production (Toledo et al, 2009and Ferreira et al, 2009, animal feed (Toso et al, 2009 andClark et al, 2010), electrofused grains (Luche et al, 2009), glass bottles (Almada- Lobo et al, 2007Lobo et al, , 2008, foundries (Araujo et al, 2008;Tonaki andToledo, 2010 andCamargo et al, 2012), yogurt packaging company (Marinelli et al, 2007), pharmaceutical company (Stadtler, 2011), and sand casting operations (Hans and Van de Velde, 2011).…”
Section: Introductionmentioning
confidence: 99%